(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Physical activity has been shown to enhance health, particularly for older people who typically have lower levels of physical activity. Many factors influence physical activity level, including culture and socioeconomic status, which in turn increases the risk of developing age-related conditions such as frailty and sarcopenia. The Bedford, Luton, and Milton Keynes Integrated Care Service (BLMK ICS) has developed a screening and intervention programme called the Healthy Ageing Programme (HAP) which identifies people at risk of frailty and sarcopenia. The programme has been developed as a pilot in Luton, which is a town in the BLMK area that has a culturally diverse population. Project Description: The project is co-produced with a diverse group of stakeholders, including older community members from many different cultures, leaders within these communities, members of local authorities, as well as professionals in health and social care. People at risk of developing frailty and sarcopenia are identified through both electronic health record screening, for people who routinely access primary care, while community-based screening is used to ensure people that do not routinely access health and social care services are included. The interventions were also co-developed, with activities chosen based on the preferences of participants and scientific literature. The range of activities cover a wide spectrum, including walking sports such as football and cricket, golf, chair-based activities, as well as fitness classes and gym membership. A mixed methods evaluation includes pre- and post- assessment of physical function and quality of life, while pre- and post-intervention interview enable attitudes and experiences to be explored. The project will be scaled up to other areas within the BLMK Region, contingent upon results of this pilot study. Final result of the study will be disseminated via academic publications, while discussions have started with neighbouring areas of the United Kingdom looking to adopt a similar approach. Conclusion: Co-producing a screening programme to identify the increase of people at risk of frailty and sarcopenia, followed by co-developing bespoke interventions, has the potential to increase physical activity levels in older people.